A cultural and discoursal prospect toward Persian literary translation assessment - Amirdabbaghian, Amin (Jahan Elm Institute of Higher Education, 2016)
The role of discourse and discoursal elements in the formation of any text is very important. Many scholars have carried out studies related to the issue. Transferring these elements from one language to another is such a great work that translators find it difficult to render and transfer the elements completely. The lack of perfect knowledge of the discoursal issues and other contextual elements of a text leads to some misunderstandings and mistranslations. Translators often resort to adaptation in order to deal with the SL situations that do not exist in the tl but in this process some discoursal and contextual elements of the ST could not be transferred. It could be claim that a nation’s literature is a part of its discourse and cultural elements are embedded in the literature. These translational conflicts are more obvious in contemporary Persian literature. In this study, the selected parts of “The Gambler” by “Fyodor Mikhailovich Dostoevsky” were compared with its English translations by Saleh Hosseini to find out whether the discourse and other contextual elements of the source text have been considered in the process of translation.